2022
DOI: 10.1155/2022/1716087
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of algD, pslD, pelF, Ppgl, and PAPI-1 Genes Involved in Biofilm Formation in Clinical Pseudomonas aeruginosa Strains

Abstract: Introduction. Biofilm formation is one of the main virulence factors in Pseudomonas aeruginosa infections. This study is aimed at investigating the presence of genes involved in biofilm formation in clinical P. aeruginosa isolates. Material and Methods. A cross-sectional study was conducted on 112 P. aeruginosa isolates. The biofilm formation assay was performed on all isolates. Antimicrobial resistance was determined by the disk diffusion method, and the presence of genes was detected by polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Today, biofilm infection therapy is challenging for clinicians. Biofilm-related infections cannot be effectively treated with antibiotics; but understanding how biofilms work can assist us in fighting them [ 18 , 19 ]. Thus, today many studies are looking for new approaches to overcoming biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, biofilm infection therapy is challenging for clinicians. Biofilm-related infections cannot be effectively treated with antibiotics; but understanding how biofilms work can assist us in fighting them [ 18 , 19 ]. Thus, today many studies are looking for new approaches to overcoming biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…algD is another important gene involved in P. aeruginosa biofilm formation and antibiotic resistance. According to Rajabi et al, the algD gene is present in 78.6% of P. aeruginosa strains and it plays an important role in biofilm formation [ 19 ]. Our data showed that the expression of algD expression reduced significantly in the presence of EcN OMVs (50 µg).…”
Section: Discussionmentioning
confidence: 99%
“…Target genes were selected based on a literature review of genes involved in the production of extracellular matrix components needed for biofilm formation. We searched for relevant genes previously reported in Pseudomonas aeruginosa ( alg 44, algD, algU, fimX, lecA, lecB, pelD, pelF, pslD ) [ [93] , [94] , [95] ], Pseudomonas putida ( bcs, pea, peb ) [ 96 ], and Stenotrophomonas maltophilia ( rmlA and spgM ) [ 97 ]. To the best of our knowledge, genes involved in the production of extracellular matrix components have not been reported for Microbacteriaceae or Flavobacteriaceae .…”
Section: Methodsmentioning
confidence: 99%
“…Biofilm is defined as an assemblage of microbial cells that are attached to a surface and enclosed in an extracellular matrix principally made of polysaccharide material [ 15 17 ]. Biofilm is considered an important virulence factor and plays a significant role in antibiotic resistance [ 18 ].…”
Section: Introductionmentioning
confidence: 99%